2012
DOI: 10.17221/58/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MON 810 cultivation and prevention to adventitious presence in non-GM fields: A case study in Slovakia

Abstract: Mihalčík P., Hrčková K., Singer M., Plačková A., Kraic J. (2012): Effect of MON 810 cultivation and prevention to adventitious presence in non-GM fields: A case study in Slovakia. Plant Protect. Sci., 48 (Special Issue): S11-S17.The efficiency of border rows to prevent the adventitious presence of GM maize in non-GM maize plots was evaluated as well as the effect of the MON 810 maize of the yield and self-protection against the European corn borer. The GM maize MON 810 event was drilled at 3 locations over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
2
4
0
Order By: Relevance
“…The farmers who were interviewed found the yield to be dependent on climatic conditions and pest infestation. Their observations agree with studies reporting that the yield increase depends highly on the climatic conditions of the growing season (Kocourek and Stará, 2012) and on ECB pressure (Křístková, 2009;Wolf and Vögeli, 2009;Mihalčík et al, 2012). Bt maize MON810 provided a small increase in yields or almost none at all in years with low corn borer infestation and 15-25% increase under high pest pressure in Czech variety trials (Křístková, 2009).…”
Section: "Yield Increase Thanks To Intact and Healthysupporting
confidence: 87%
See 2 more Smart Citations
“…The farmers who were interviewed found the yield to be dependent on climatic conditions and pest infestation. Their observations agree with studies reporting that the yield increase depends highly on the climatic conditions of the growing season (Kocourek and Stará, 2012) and on ECB pressure (Křístková, 2009;Wolf and Vögeli, 2009;Mihalčík et al, 2012). Bt maize MON810 provided a small increase in yields or almost none at all in years with low corn borer infestation and 15-25% increase under high pest pressure in Czech variety trials (Křístková, 2009).…”
Section: "Yield Increase Thanks To Intact and Healthysupporting
confidence: 87%
“…Isolated findings of caterpillars' activity may also be explained by their immediate identification after they got to the Bt maize from another host plant (Křístková, 2009). Other studies also reported a negligible extent of damaged stalks and ears of Bt maize plants in field trials in Europe and the USA (events MON810, Bt176 and stacks including MON810) but overall highly effective control of the ECB (Magg et al, 2001;Mihalčík et al, 2012;Bohnenblust et al, 2014).…”
Section: "100% Control Of European Corn Borer During the Whole Periodmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, in Slovakia, one border row can replace a 2-m isolation distance (Mihalčík et al, 2012), and, in Portugal, a 200-m isolation distance can be replaced by 24 border rows (De Fatima Quedas and Cruz de Carvalho, 2012). This border may, on one side, act as a physical pollen barrier and, on the other side, may compete with the GM pollen by shedding its own non-GM pollen.…”
mentioning
confidence: 99%
“…Therefore, non-GM maize borders have found their way into the coexistence regulations of several EU member states and can be used to reduce the prescribed isolation distances. For example, in Slovakia, one border row can replace a 2-m isolation distance (Mihalčík et al, 2012), and, in Portugal, a 200-m isolation distance can be replaced by 24 border rows (De Fatima Quedas and Cruz de Carvalho, 2012). Even though the scientific indications for the efficacy of border rows are extremely scarce (Rühl et al, 2011), this measure fulfills the demand of non-GM maize growers as a coexistence measure that should be implemented by the farmer growing GM maize (Devos et al, 2009).…”
mentioning
confidence: 99%